Covid-19 Patient Transport: A Literature Review - Aisah, Siti; Nurhidayati, Tri; Setyawati, Dewi; Muntoha, Mohammad Gita (University of Muhammadiyah Semarang, 2022)
The pandemic caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (COVID-19) is tremendously affecting health care services worldwide due to the nature of this virus which is highly infectious with a high rate of transmission. Transmission of the COVID-19 virus quickly occurs through close contact, droplet, airborne, and faecal-oral. During the prevention and containment of the pandemic, ambulances play an important role in transporting infectious patients. Health workers working in ambulances are at high risk of contracting the COVID-19 virus considering an ambulance is a small, confined and enclosed compartment. It is necessary to find a safe way of transporting COVID-19 patients by ambulance. Methods This thesis uses a literature review method. By following the PRISMA flow diagram, research journals are gathered from the electronic database Sciencedirect and Pubmed by performing keyword searches. The results are then sorted based on predefined inclusion criteria. Nine original research journals are obtained and reviewed. Results we found a variety of control measures that can be applied in transporting COVID-19 patients safely. These control measures can be categorised using the Control Hierarchy approach which includes elimination, engineering control, administrative control and usage of personal protective equipment (PPE). Conclusion transportation of COVID-19 patients by ambulance can be carried out safely by strictly adhering to the control measures and certain protocols found in this literature review These control measures can be categorised using the Control Hierarchy approach which includes elimination, engineering control, administrative control and usage of personal protective equipment (PPE). Conclusion transportation of COVID-19 patients by ambulance can be carried out safely by strictly adhering to the control measures and certain protocols found in this literature review These control measures can be categorized using the Control Hierarchy approach which includes elimination, engineering control, administrative control and usage of personal protective equipment (PPE). Conclusion transportation of COVID-19 patients by ambulance can be carried out safely by strictly adhering to the control measures and certain protocols found in this literature review.